2008
DOI: 10.1017/s1551929500059782
|View full text |Cite
|
Sign up to set email alerts
|

Hardware and Techniques for Cross- Correlative TEM and Atom Probe Analysis

Abstract: IntroductionAtom probe tomography has primarily been used for atomic scale characterization of high electrical conductivity materials [1]. A high electrical field applied to needle-shaped specimens evaporates surface atoms, and a time of flight measurement determines each atom's identity. A 2-dimensional detector determines each atom's original position on the specimen. When repeated successively over many surface monolayers, the original specimen can be reconstructed into a 3-dimensional representation. In or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
70
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 7 publications
2
70
0
Order By: Relevance
“…As recently reviewed by Herbig,8 full electron microscopy characterization of specific features can be carried out on needle-shaped specimens prior to APT analysis by utilizing specially designed holders. This approach has, for example, led to a better understanding of diffusional mechanisms resulting in local solute segregation at crystalline imperfections [9][10][11][12][13][14] that critically impact the macroscopic material behavior. APT had previously revealed details of the composition of structural imperfections, 15 the presence of which were confirmed by field ion microscopy 16 or TEM.…”
Section: Introductionmentioning
confidence: 99%
“…As recently reviewed by Herbig,8 full electron microscopy characterization of specific features can be carried out on needle-shaped specimens prior to APT analysis by utilizing specially designed holders. This approach has, for example, led to a better understanding of diffusional mechanisms resulting in local solute segregation at crystalline imperfections [9][10][11][12][13][14] that critically impact the macroscopic material behavior. APT had previously revealed details of the composition of structural imperfections, 15 the presence of which were confirmed by field ion microscopy 16 or TEM.…”
Section: Introductionmentioning
confidence: 99%
“…However, study of the multi-phase material that results from controlled cooling of the single phase material can provide insight into the destabilization mechanisms and methods of manipulating the microstructure. The correlated use of transmission electron microscopy (TEM) and atom probe tomography (APT) is well-suited for such analyses [3,4].Here, the previously presented Mg0.2Ni0.2Co0.2Cu0.2Zn0.2O (E1) sample [1] is explored after air quenching from 1000 °C to room temperature and after slow cooling in a furnace at 2 °C/min to room temperature. APT specimens were prepared from the bulk samples using a modified focused ion beam (FIB) lift-out technique [5] where specimens were mounted on TEM grids in holders compatible with the FIB, TEM, and APT instruments [3].…”
mentioning
confidence: 99%
“…The correlated use of transmission electron microscopy (TEM) and atom probe tomography (APT) is well-suited for such analyses [3,4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to fully characterize the tip geometry, hardware was developed that allows for cross sectional tomographic imaging of W wire shaped tips in a modern TEM or STEM, along with FIM, Atom Probe Tomography, and imaging in a UHV STM [4]. During characterization of the tip geometries using SEM, TEM, FIM, and atom probe, it was found that the tip radius was several orders of magnitude larger than expected (Fig 1).…”
mentioning
confidence: 99%